Laser optoacoustic method for investigation of some physical parameters of oil and oil products - Musaev, Musaver Abdulsalam; Abbasov, Ibrahim Isa; Abdullaeva, Gulshan Kamal (Eastern-European Journal of Enterprise Technologies, 2017)
An operational laser optoacoustic method, which allows simultaneous determination of the light absorption coefficient and the speed of sound in oil and oil products is proposed and experimentally implemented. These values are the most important parameters of oil. The existing traditional methods for measuring these quantities are complex, as they involve the use of quartz converters, optics, etc. The method is based on investigating the front of the optoacoustic signal and measuring the speed of acoustic pulses in the samples. Acoustic pulses are produced by the thermo-optical mechanism of ultrasound excitation when the radiation pulse of a neodymium laser falls at a wavelength of 1.06 μm for 20 ns on the surface of the medium. The resulting temperature gradient causes additional mechanical stresses. These stresses are the sources of acoustic waves that propagate from the heat-release zone. Since the leading edge of the pulse is formed by a straight wave propagating directly from the border, its profile repeats the spatial distribution of stress sources. For a homogeneous liquid, the theoretically calculated form of the thermo-acoustic compression pulse has a simple form p’ exp(–αz) (p’ is the excess pressure in the depth z of the medium, and α is the absorption coefficient of the laser radiation in the medium). The measured values of the absorption coefficient for various oils were 2–40 cm-1. Based on the proposed method, the method for determining the temperature coefficient of sound speed and oil tarness was developed